Quantifying heterogeneity of physical and mental health-related quality of life in chronic obstructive pulmonary disease patients in the United States. (1st September 2020) - Shah, Chintal H.; Reed, Robert M.; Villalonga-Olives, Ester; Slejko, Julia F.; Eakin, Michelle N.; So, Jennifer Y.; Zafari, Zafar
ABSTRACT: Background: Chronic obstructive pulmonary disease (COPD) is a heterogenous condition. This study aims to quantify the heterogeneity of Health-related Quality of Life (HRQoL), and identify subgroups with the lowest HRQoL, in COPD patients in the United States (US). Methods: Data from 2008–2015 Medical Expenditure Panel Survey were used to examine the heterogeneity of HRQoL between different COPD subgroups using mixed-effects modeling and G-computation. The Physical Composite Summary (PCS) and Mental Composite Summary (MCS) scores from the Short-Form-12 questionnaire were utilized. We also compared the heterogeneity of HRQoL in our COPD cohort against that in a matched non-COPD cohort. Results: The final sample consisted of 1, 866 (weighted = 19, 952, 143) COPD patients with a mean age of 63.2 years (Standard error (SE):0.38), mean MCS score of 46.84 (SE:0.35), and mean PCS score of 35.65 (SE:0.32). The adjusted MCS and PCS scores ranged from 36.19 to 53.06, and from 25.52 to 48.27, respectively, for COPD subgroups. COPD patients had statistically significantly lower MCS and PCS scores by 4.61, and 5.86 points, respectively, compared to the matched non-COPD cohort, and MCS scores showed a wider variability in the COPD cohort. Conclusion: Our study quantifies substantial heterogeneity of HRQoL in COPD in the US and provides evidence for prioritizing COPD subgroups with the lowest HRQoL for targeted interventions.